88 Cardiopulmonary Exercise Testing and Prognosis in Hypertrophic Cardiomyopathy. (31st May 2014) - Coats, Caroline; Rantell, Khadija; Bartnik, Ola; Patel, Amour; Mist, Bryan; McKenna, William; Elliott, Perry
Abstract : Background: Exercise testing is commonly performed in patients with hypertrophic cardiomyopathy (HCM) to evaluate blood pressure response, a conventional risk factor for sudden cardiac death. The 2011 ACCF/AHA guidelines state "the role of metabolic stress testing in the evaluation of patients with HCM remains to be decided, particularly with regard to clinical outcome. Methods and results: Between 1998 and 2010, 1, 898 patients (age 47 ± 15 years, 67% male) with HCM underwent cardiopulmonary exercise testing (CPX). During a mean follow-up of 5.8 ± 4 years, 178 (9.4%) patients reached the primary endpoint of all-cause mortality or orthotropic heart transplant. Peak oxygen consumption, V˙O2 (HR 0.91 95% CI 0.89–0.93, p < 0.001), ventilatory efficiency, V˙EV˙CO2 (HR 1.08 95% CI 1.06–1.09), and ventilatory anaerobic threshold V˙AT (HR 0.88 95% CI 0.84–0.92) were predictors of the primary outcome. A progressively worse prognosis was associated with higher ventilatory class (Figure 1 ). V˙EV˙CO2 was a good predictor of heart failure death or transplantation (HR 1.1 95% CI 1.07–1.14 p < 0.001) outcome but not sudden cardiac death (HR 1.01 95% CI 0.97–0.96 p = 0.54). Conclusions: CPX provides important prognostic information in patients with HCM. Sub-maximal exercise parameters are potentially more useful than peak VO2 alone. Patients with an enhanced ventilatory response have a substantially higher risk of death or transplantation. Reference: 1 Gersh, et al . JACC 2011;58(25):212–60